AL-QUR`AN DALAM MERESPONS FENOMENA HOAX: Kajian Tafsir Tematik - Moch Arifin (AL ITQAN: Jurnal Studi Al-Qur'an, 2018)
One of the social problems in the world, especially in Indonesia today, is the prevalence of hoax reported  in various mass media. The emergence of this news not only confuses various levels of society, but even defames the reputation of certain parties. This article aims to explain how the view of the Qur'an in responding to the hoax phenomenon. By using the thematic interpretation approach initiated by al-Farmāwī, the author aims to describe the verses of the al-Qur`an which are related to the issue of news and the story of ḥadīts al-ifk that afflicted 'Āisyah.